Pengaruh lama penyimpanan biji dan beberapa media perkecambahan terhadap daya kecambah biji Pinanga javana - Helmanto, Hendra; Damayanti, Frisca; Yudaputra, Angga; Zulkarnaen, Rizmoon Nurul; Latifah, Dian (Innovation Centre for Tropical Sciences, 2024)
The IUCN red listed Pinanga javana Blume, also known as Javanese Pinang, as a protected and threatened species that is endemic to Java island, Indonesia. This research focused on study of the germination and growth process of P. javana seedlings using four types of planting media: cocopeat, husks, sand, and sawdust. The results showed that P. javana seed water content slowly decreased from 33.96% to 24.45% during the storage period from day 0 to day 21. The planting medium had a significant influence on the germination rate, with sand exhibiting the highest value (2.34) and husks providing the best seedling growth. Cocopeat had the highest moisture level (90%), while sand generated the lowest moisture level. The pH of all media was within the normal range (6-7), which supports optimal germination. The analysis of various parameters concluded that sand was the optimal planting medium for P. javana in this study. Keywords: germination, planting media, Pinanga javana, viability, water content